54 ÷ 6 + 36 + 9 = 54
28 plus 17 plus 25 plus 54 plus 20 plus 36 is equal to 180.
18 + 36 + 45 + 9 + 9 + 54 + 27 + 72 + 81 = 351
18(2 + 3)
6x + 18 = 54 6x = 54 - 18 6x = 36 x = 36 ÷6 x = 6
54 ÷ 6 + 36 + 9 = 54
It is the same as 54 plus 36 and both expressions add to 90
54
28 plus 17 plus 25 plus 54 plus 20 plus 36 is equal to 180.
4x + 4 + 14 = 54 4x + 18 = 54 4x = 54 - 18 4x = 36 x = 36/4 x = 9 Check: 4(9) + 4 + 14 = 54 36 + 18 = 54 54 = 54
18 + 36 + 45 + 9 + 9 + 54 + 27 + 72 + 81 = 351
18(2 + 3)
6x + 18 = 54 6x = 54 - 18 6x = 36 x = 36 ÷6 x = 6
18 plus 18 plus 18 equals 54. This can be calculated by adding the first two 18s together to get 36, and then adding the third 18 to get the final sum of 54. This is a basic arithmetic operation involving addition of three numbers.
It is: 18(2+3) or simply as 90
It is: 36/54 = 2/3
The LCM of 36 and 54 is 108.